2019
DOI: 10.2174/1874467212666181126151948
|View full text |Cite
|
Sign up to set email alerts
|

Does the Development of Vaccines Advance Solutions for Tuberculosis?

Abstract: Background: Mycobacterium tuberculosis (Mtb) is considered as one of the most efficacious human pathogens. The global mortality rate of TB stands at approximately 2 million, while about 8 to 10 million active new cases are documented yearly. It is, therefore, a priority to develop vaccines that will prevent active TB. The vaccines currently used for the management of TB can only proffer a certain level of protection against meningitis, TB, and other forms of disseminated TB in children; however, their effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 242 publications
0
2
0
Order By: Relevance
“…The result showed that anionic liposomes are efficient when Th1 responses increase 14 . Some of the cationic liposomal adjuvants that progressed to human clinical trials are JVRS‐100, Vaxfectin, CAF01, and LPD 54 . The main component of CAF01 comprises the cationic liposome dimethyl‐dioctadecyl ammonium (DDA); it contains the hydrophilic head group of dimethylammonium bonded to two hydrophobic 18‐carbon alkyl chains 55 .…”
Section: Physicochemical Properties Of Liposomal Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that anionic liposomes are efficient when Th1 responses increase 14 . Some of the cationic liposomal adjuvants that progressed to human clinical trials are JVRS‐100, Vaxfectin, CAF01, and LPD 54 . The main component of CAF01 comprises the cationic liposome dimethyl‐dioctadecyl ammonium (DDA); it contains the hydrophilic head group of dimethylammonium bonded to two hydrophobic 18‐carbon alkyl chains 55 .…”
Section: Physicochemical Properties Of Liposomal Adjuvantsmentioning
confidence: 99%
“…14 Some of the cationic liposomal adjuvants that progressed to human clinical trials are JVRS-100, Vaxfectin, CAF01, and LPD. 54 The main component of CAF01 comprises the cationic liposome dimethyl-dioctadecyl ammonium (DDA); it contains the hydrophilic head group of dimethylammonium bonded to two hydrophobic 18carbon alkyl chains. 55 DDA spontaneously separates into two vesicular layers in an aqueous medium and is used as a way of transferring antigens due to this feature.…”
Section: Physicochemical Properties Of Liposomal Adjuvantsmentioning
confidence: 99%